(3cJGH jTJed Ydi eSJMSf GdCNHGQ hZQjH GdMcGjGJ hQGFb GdCTYGQ hCMGOjK GdChGFd hGdBKGQs
(3ChdgG (B:s
(3Gddge EfG fMeOc Ydi eG CfYeJ CejQ GdeDefjf CHj GdaQGA ehdGfG ESeGYjd Hf ehdGfG GdTQja s
(3BNQgG (B:s
(3hEf GdEMSGf Edjge cQe hGdEYQGV Yfge dDe hfOe aGSJOQc aQW JaQjWc hef GdCZGfi (B: (3eYO Hf YOfGf Hf ESeGYjd Hf EHQGgje Ydjge GdSdGe GfJgi s
(3HgG fXGe GdJYbjHIs
(3LeY ddSdWGf ESeGYjd Hf GdTQja GdYdhis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B159 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs